The Freshwater Biodiversity Information System (FBIS) – mobilising data for evaluating long-term change in South African rivers. Issue 3 (14th October 2022) - Dallas, Helen; Shelton, Jeremy; Sutton, Tim; Tri Cuptura, Dimas; Kajee, Mohammed; Job, Nancy
Abstract : Access to long-term biodiversity datasets is vital for monitoring, managing and protecting freshwater ecosystems. Detecting critical ecosystem changes, such as losing unique biodiversity and ecosystem services, is dependent on access to data. A wealth of biodiversity data exists for river ecosystems in South Africa, but an operational information system to access these data is currently not available. This gap is the result of limited capacity for managing freshwater biodiversity data, with existing systems isolated, difficult to access and not well maintained. To address this knowledge gap, the Freshwater Biodiversity Information System (FBIS) has been developed. The FBIS is a powerful, visual, data-rich information system for hosting and serving freshwater biodiversity data. It serves as a platform for the inventory and maintenance of data, thereby facilitating the evaluation of long-term change in river biodiversity and ecosystem condition, and guiding future monitoring strategies and management decisions. System design and functionality was strongly informed by data and reporting needs of key end-user groups, including water resource managers, biodiversity and conservation managers and planners, scientific researchers, and environmental consultants. Future expansion aims to increase the diversity of data accessed, data flow, geographic coverage and strategically embed FBIS into South Africa's main freshwater decision-making pipelines.